WORK PERFORMANCE IN THE RETAIL INDUSTRY: AN ANALYSIS OF THE ROLE OF WORK EXPERIENCE, EMPLOYEE ENGAGEMENT, AND EXTRINSIC MOTIVATION - Khusniah, Khasin; Winahyu, Pawestri; Nursaidah, Nursaidah (Univesitas Muhammadiyah Tangerang, 2025)
Human resources play a key role in achieving an organization's competitive advantage. This study analyzes the influence of work experience, organizational commitment, and extrinsic motivation on employee performance at Dira Pontang Shopping Center. This study contributes to the human resource management literature by examining integrative models in the context of Indonesian retail which is still limited in research. The quantitative method was applied using multiple linear regression analysis on primary data collected through questionnaires and observations of 76 employees (saturated sampling). The results show that work experience, organizational commitment, and extrinsic motivation have a significant positive effect on employee performance. These findings strengthen the HR theory by affirming the importance of a holistic approach in improving performance. The novelty of the research lies in the unique combination of the three variables in a local retail setting. Practically, management can improve performance through the development of training programs, strengthening organizational commitments, and optimizing the reward system. This study recommends further studies by adding mediator variables to enrich the model.